ASSESSMENT OF HYBRIDIZATION RATIO FOR A SMALL HYBRID-ELECTRIC BUSINESS JET - Alibek, Arailym (School of Engineering and Digital Sciences, 2023)
Within recent decades, the development of aerial vehicles with Hybrid-Electric Propulsion Systems (HEPS) has evolved into aerospace thanks to their simple incorporation of efficient powertrains. Increasing environmental concerns about traditional fuel-based propulsion systems drove major corporations to hybridize classical aircraft to minimization of CO2, noise, and other hazardous particles by 70%. As the mission complexity among both civilian and military applications includes landing and take-off which are power-demanding, the use of hybrid-electric is necessary to overcome the deficiency of all-electric vehicles. This thesis is primarily concerned with the development of a HEPS for a medium-range aircraft. Considered aircraft is assessed on the various hybridization ratio to estimate the optimal. Moreover, the propulsion is analyzed according to a power-based conceptual sizing methodology. During the procedure, mass distribution for five different architectures, which are all-electric, pure combustion, series, and parallel HEPS, have been simulated. For the simulation, the choice of aircraft has been chosen according to the maximum range value of more than 1000 km, which Zunum Aero ZA10 can acquire. Moreover, the thesis conducted research on three different areas of interest such as hybrid aircraft, quiet takeoff and landing, and quiet cruise target. The outcomes indicate that the hybrid design of medium-range aircraft is an optimal solution both for researchers and practitioners. Between series and parallel hybrid configurations, the comparison indicates that the latter is an ideal choice for the practitioners as it can be applied for all the considered research interest areas, whereas the series is shown as a maximum footprint reduction tool. The thesis has contributed significantly to the knowledge of HEPS for middle-range aircraft, and the findings can be applied for the improvement of the initial performance of aircraft under specific constraints. The study has provided insights into the best ratio of fuel and battery weights for such aircraft and has compared HEPS performance in the same mission profile and speed parameters. The research has limitations, and further research is needed to combine the sizing procedure for HEPS with the actual aircraft design, explore advancements in battery and engine technology, and consider the multi-disciplinary optimization of HEPS.
Keywords: type of access: open access; Hybrid-electric propulsion system; Zunum aircraft; Power-based sizing methodology; Propulsion configurations simulation